Homerange Ophiophagus hannah Cantor, 1836 in Oil Palm Plantation in Central Kalimantan - Origia, Kevin; Novarino, Wilson; Silmi, Muhammad; Tjong, Djong Hon (Metamorfosa: Journal of Biological Sciences, 2019)
Fragmentation habitat affected homerange animals, which one is King cobra. King cobra was founded in palm oil plantation because palm oil plantation provide new habitat for king cobra. King cobra homerange overlaping with other king cobra’s but the homerange areas different, due to the difference of obervation time. Microhabitat temperature, environtment temperature and humidity influences homerange of king cobra’s.environmental factor also affect king cobra homerange. Daily activity of king cobra and human activity near the king cobra habit also affect  the homerange. Hunting activity of king cobra most affected factor to changes homerange king cobra. The large avalaibility of prey leads to hunting area decrease and narrow the hunting area of king cobra. Keywords : Radiotelemetry, king cobra, homerange, environment factor